Organic-inorganic hybrid perovskite laser based on DFB structure and preparation method of gain medium
By adopting DFB structure and organic-inorganic hybrid perovskite film in the laser and integrating periodic gratings, the technical challenges of traditional lasers in single-mode output and pumping efficiency are solved, and efficient and stable single-mode laser output is achieved. , suitable for applications such as fiber optic communication.
Patent Information
- Application Number
- CN202411700370.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-21
AI Technical Summary
Traditional lasers have technical challenges in single-mode output and pumping efficiency, especially in nanosecond laser pumping conditions, which are difficult to achieve efficient optical gain and laser output.
Using an organic-inorganic hybrid perovskite laser based on DFB structure, a single-mode laser output is achieved by integrating a periodic grating in the gain medium. The laser uses an organic-inorganic hybrid perovskite film as the gain medium and uses femtosecond or nanosecond lasers as the pumping source to achieve single-photon or multi-photon pumping.
It realizes efficient and stable single-mode laser output, improves the stability and purity of the spectrum, lowers the laser starting threshold, enhances tuning capability and stability, and is suitable for high-precision applications such as optical fiber communication.
Smart Images

Figure CN119496046A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lasers, and in particular to a method for preparing an organic-inorganic hybrid perovskite laser and a gain medium based on a DFB structure. Background Art
[0002] As an important light source, lasers are widely used in communications, sensing, material processing, display technology and other fields. In recent years, with the rapid development of optoelectronic technology, the application demand for lasers with high efficiency, stability and low threshold continuous wave operation has increased. Perovskite materials, especially organic-inorganic hybrid perovskites, have made significant progress in the fields of photodetectors, solar cells and light-emitting devices due to their unique optoelectronic properties, including adjustable band gap, high absorption coefficient and excellent carrier mobility. In particular, as a laser gain medium, perovskite materials exhibit low threshold and high gain laser emission characteristics.
[0003] Distributed Bragg reflector (DBR) lasers and distributed feedback (DFB) lasers are both common types of semiconductor lasers, both of which use grating structures to provide optical feedback. The optical feedback of a DBR laser is provided by Bragg reflectors located at both ends of the gain region, which are located outside the gain region. The emission wavelength of the laser is determined by the grating period of the Bragg reflector, and the active region does not directly participate in the feedback. Since the feedback mechanism is located outside the gain region, the feedback efficiency is low, which may cause the single-mode purity of the laser output to be inferior to that of a DFB laser. The mode selection of DBR lasers is weak and it is easy to induce multi-mode output (Wang K, Wang S, et al., Advanced Optical Materials, 2018, 1800278; Liu A, Guan G, et al., Laser & Photonics Reviews, 2022, 2200189). The periodic grating in the DFB laser is distributed throughout the gain region, and the grating interacts with the light in the gain region to produce a strong feedback mechanism. Feedback and gain exist in the same region at the same time, producing single-mode output. DFB lasers have strong single-mode characteristics, narrow spectral linewidth, and stable output power, and are suitable for applications that require precise wavelength control, such as fiber-optic communications. Due to the high feedback efficiency, the gain and feedback mechanisms are highly integrated and have good tuning stability. The Chinese patent application publication number CN118739026 A proposes a distributed feedback quantum dot laser, in which the quantum dots need to be dispersed in a curing glue, and a nanoimprinting process is used to obtain a grating structure. However, the grating obtained by nanoimprinting technology is usually irregular, which is not conducive to generating optical gain. The Chinese patent application publication number CN108011292A discloses DBR and DFB lasers based on colloidal quantum dots, but the laser uses colloidal quantum dots as the gain medium, but the colloidal quantum dot film has a large scattering, resulting in the output of multi-mode lasers.
[0004] Under the action of various pump sources, due to the small thermal effect, it is easy to realize femtosecond laser pumped organic-inorganic hybrid perovskite laser. The literature (Advanced Optical Materials 18, 2018, 1800278. https: / / doi.org / 10.1002 / adom.201800278) points out that when nanosecond laser is used to pump organic-inorganic hybrid perovskite film, it is usually difficult to generate optical gain or laser output due to the high threshold and thermal effect.
[0005] Therefore, the present invention provides an organic-inorganic hybrid perovskite laser based on a DFB structure, which realizes single-mode laser output pumped by nanosecond and femtosecond laser light sources. Summary of the invention
[0006] In the field of laser technology, lasers using organic-inorganic hybrid perovskite as gain medium are mainly distributed Bragg reflector lasers. Since the mode selection of this type of laser is weak, it is easy to cause multi-mode output. At present, distributed feedback perovskite lasers mostly use nanoimprinting methods to make grating structures in perovskite films, which affects the structural quality of the gain layer and causes instability in laser performance. Compared with the commonly used perovskite quantum dot gain medium, organic-inorganic hybrid perovskite films have good advantages in uniformity, optical gain coefficient, gain threshold, etc. Therefore, the development of a single-mode, simple to prepare, and uniform laser has become a technical problem that needs to be solved in the field of laser technology.
[0007] The object of the present invention is to provide an organic-inorganic hybrid perovskite laser based on a DFB structure, specifically as follows: The present invention provides an organic-inorganic hybrid perovskite laser based on a DFB structure, comprising: a pump source: an ultraviolet light or blue light source to realize single-photon pumping or a near-infrared light or far-infrared light source to realize multi-photon pumping; a gain medium: an organic-inorganic hybrid perovskite film; and a resonant cavity: a substrate having a periodic Bragg grating structure.
[0008] The present invention provides a method for preparing an organic-inorganic hybrid perovskite film, comprising the following steps: S1. Accurately weigh MX, FX and PbX2 and dissolve them in a solvent to obtain MPbX3 or F2M n-1 Pb n X 3n+1 (n>1) precursor; Organic-inorganic perovskite film is prepared using S2-1 or S2-2: Using the S2-1 method, the above-mentioned precursor solution is dropped onto the surface of a rotating substrate, an anti-solvent is added after spin coating for a period of time, and then an organic-inorganic hybrid perovskite film is obtained by annealing. Using the S2-2 method, MX, FX and PbX2 are deposited on the substrate surface by evaporation, and then annealed to obtain an organic-inorganic hybrid perovskite film; X is a halogen anion; MX is one or two of formamidine hydrohalide and methylamine halide; FX is one or more of benzylamine halide, n-octylamine hydrohalide, isobutylammonium halide, phenylpropylamine halide, aminovaleric acid halide, 1-naphthylmethylammonium halide, guanidine hydrohalide, n-butylamine halide, phenylbutylamine halide, n-butylammonium halide, ethylamine hydrohalide and phenethylamine halide.
[0009] In the above scheme, the solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, γ-butyrolactone and N-methylpyrrolidone.
[0010] In the above scheme, the anti-solvent is one or more of toluene, chloroform, ethanol, chlorobenzene, ethyl acetate, and butyl acetate.
[0011] In the above scheme, the annealing temperature is 50-150 o C, annealing time is 10-120min.
[0012] In the above scheme, in the preparation step S2-1, the anti-solvent is added after spin coating for 5-30 seconds.
[0013] In the above scheme, S3-1 or S3-2 is used to prepare: The S3-1 method is used to use a periodic Bragg grating structure directly as a substrate; Using the S3-2 method: (a) Weigh polymethyl methacrylate (PMMA) and dissolve it in a solvent; (b) The PMMA solution is spin-coated on a structure having a periodic Bragg grating, and the resulting composite structure is the substrate.
[0014] In the above scheme, the substrate is prepared by S3-1 or S3-2: the solvent for dissolving PMMA includes but is not limited to carbon tetrachloride, benzene, toluene, dichloroethane, chloroform, acetone, one or more combinations thereof, and the mass fraction WT of PMMA satisfies: 0 <WT≤1wt%。
[0015] In the above scheme, the grating satisfies mλ=2nL, m is the grating order, λ is the laser output wavelength, n is the refractive index of the organic-inorganic hybrid perovskite film, and L is the period of the grating.
[0016] In the above scheme, the duty cycle of the periodic Bragg grating is 0.25-0.75.
[0017] In the above solution, the pump source is a pump light source having a wavelength shorter or longer than the absorption cutoff wavelength of the organic-inorganic hybrid perovskite.
[0018] In the above scheme, the pump source light source is ultraviolet light, blue light, near infrared light, or far infrared light.
[0019] In the above solution, the method for preparing the periodic Bragg grating includes but is not limited to laser etching, dry etching and wet etching.
[0020] In the above scheme, the pump source is a femtosecond laser or a nanosecond laser, and the laser is a single-photon or multi-photon pump laser, that is: A femtosecond laser was used as the pump source for single-photon pumping.
[0021] Femtosecond laser is used as pump source for multiphoton pumping.
[0022] Nanosecond laser is used as pump source to perform single-photon pumping.
[0023] Nanosecond laser is used as pump source to perform multiphoton pumping.
[0024] The present invention solves the technical problems of traditional lasers in single-mode output and pumping efficiency through the DFB structure organic-inorganic hybrid perovskite laser and its preparation method, and realizes efficient and stable laser output. The specific technical effects and advantages are as follows: 1. Application of DFB structure: The present invention adopts DFB (distributed feedback) structure and realizes single-mode laser output by integrating periodic grating in the gain medium. This structure effectively reduces the multi-mode emission of the laser and improves the stability and purity of the spectrum, which is particularly important for applications that require precise wavelength control, such as optical fiber communication.
[0025] 2. Advantages of organic-inorganic hybrid perovskite film: The gain medium uses an organic-inorganic hybrid perovskite film, which has the characteristics of high optical gain coefficient and low laser emission threshold. Compared with traditional laser media, such as semiconductor materials, perovskite materials show better performance in absorption efficiency and carrier mobility, thereby reducing the start-up threshold of the laser and improving the laser efficiency.
[0026] 3. Precise control of pump source: The present invention uses femtosecond laser or nanosecond laser as the pump source. These laser light sources can precisely control the energy transmission and excitation mode, thereby achieving single-photon or multi-photon pumping. This precise control not only improves the efficiency of laser output, but also enhances the tuning ability and stability of the laser.
[0027] 4. Simplicity of preparation method: The method for preparing organic-inorganic hybrid perovskite film is simple and efficient, which can be achieved by solution method or evaporation technology. This method not only simplifies the production process, but also ensures the uniformity and stability of the film, which is crucial to improving the performance of lasers.
[0028] 5. Flexibility of grating design: The design of periodic Bragg grating is flexible, and the period and duty cycle of the grating can be adjusted as needed to meet the needs of different wavelength outputs. This design gives the laser significant advantages in wavelength tuning and stability.
[0029] 6. Wide application fields: Due to the advantages of the present invention in single-mode output, efficient pumping and stability, it has broad application prospects in high-precision application fields such as optical fiber communication, laser printing, and medical imaging.
[0030] In summary, the present invention provides an efficient, stable, and easy-to-prepare laser solution in the field of laser technology, which has significant technical advantages and broad application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the laser structure of the present invention, wherein (a) corresponds to Example 1, and (b) corresponds to Example 2.
[0032] Figure 2 Atomic force microscope images of the organic-inorganic perovskite film in the laser prepared by the present invention, wherein (a) corresponds to Example 1, and (b) corresponds to Example 2.
[0033] Figure 3 The normalized fluorescence spectrum curves of the organic-inorganic perovskite film in the laser prepared by the present invention, wherein (a) corresponds to Example 1, and (b) corresponds to Example 2.
[0034] Figure 4 Optical gain spectrum of the organic-inorganic perovskite film prepared in the present invention under the action of a femtosecond laser (excluding the DFB structure).
[0035] Figure 5 The laser output characteristic curve and spectrum diagram before and after the threshold of the perovskite laser based on the DFB structure prepared in Embodiment 1 of the present invention are shown in FIG. (a) is the spectrum curve, (b) is the different spectrum regions, and (c) is the output characteristic curve.
[0036] Figure 6 Optical gain spectrum of the organic-inorganic perovskite film prepared in the present invention under the action of nanosecond laser (excluding DFB structure).
[0037] Figure 7 The laser output characteristic curve and spectrum before and after the threshold of the DFB structure perovskite laser prepared in Example 1 are shown in Figure 1. (a) is the spectrum curve, (b) is the different spectrum regions, and (c) is the output characteristic curve.
[0038] Explanation of reference numerals: 1 - organic-inorganic hybrid perovskite film, 2 - PMMA, 3 - DFB. DETAILED DESCRIPTION
[0039] The following is a detailed description of the embodiments of the present invention. Although the present invention will be described and illustrated in conjunction with some specific embodiments, it should be noted that the present invention is not limited to these embodiments. On the contrary, modifications or equivalent substitutions made to the present invention should all be included in the scope of the claims of the present invention.
[0040] In addition, in order to better illustrate the present invention, numerous specific details are given in the following specific embodiments. It will be understood by those skilled in the art that the present invention can also be implemented without these specific details.
[0041] The invention provides an organic-inorganic hybrid perovskite laser based on a DFB structure. The laser comprises a pump source, a gain medium and a resonant cavity.
[0042] In the above solution, the pump source is a pump light source having a wavelength shorter or longer than the absorption cutoff wavelength of the organic-inorganic hybrid perovskite.
[0043] In the above scheme, the pump source light source is ultraviolet light, blue light, near infrared light, or far infrared light.
[0044] In the above solution, the gain medium is an organic-inorganic hybrid perovskite film.
[0045] The present invention provides a method for forming an organic-inorganic hybrid perovskite film, comprising the following steps: S1. Accurately weigh MX, FX and PbX2 and dissolve them in a solvent to obtain MPbX3 or F2M n-1 Pb n X 3n+1 (n>1) precursor; Organic-inorganic perovskite film is prepared using S2-1 or S2-2: The S2-1 method is used to drop the above-mentioned precursor solution onto the surface of a rotating substrate, and an anti-solvent is added at the same time, and then an organic-inorganic hybrid perovskite film is obtained by annealing.
[0046] Using the S2-2 method, MX, FX and PbX2 are deposited on the substrate surface by evaporation, and then annealed to obtain an organic-inorganic hybrid perovskite film.
[0047] In the above scheme, X is a halogen anion; MX is one or two of formamidine hydrohalide and methylamine halide; FX is one or more of benzylamine halide, n-octylamine hydrohalide, isobutylammonium halide, phenylpropylamine halide, aminovaleric acid halide, 1-naphthylmethylammonium halide, guanidine hydrohalide, n-butylamine halide, phenylbutylamine halide, n-butylammonium halide, ethylamine hydrohalide and phenethylamine halide.
[0048] In the above scheme, the solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, γ-butyrolactone and N-methylpyrrolidone.
[0049] In the above scheme, the anti-solvent is one or more of toluene, chloroform, ethanol, chlorobenzene, ethyl acetate, and butyl acetate.
[0050] In the above scheme, the annealing temperature is 50-150 o C, annealing time is 10-120min.
[0051] In the above scheme, in the preparation step S2-1, the anti-solvent is added after spin coating for 5-30 seconds.
[0052] The present invention also provides a resonant cavity of the laser, which is a periodic Bragg grating structure.
[0053] In the above scheme, the substrate is prepared by S3-1 or S3-2: The S3-1 method is adopted, and the periodic Bragg grating structure described above is directly used as a substrate.
[0054] Using the S3-2 method: (a) Weigh polymethyl methacrylate (PMMA) and dissolve it in a solvent; (b) The PMMA solution is spin-coated on a structure having a periodic Bragg grating, and the resulting composite structure is the substrate.
[0055] In the above scheme, the solvent for dissolving PMMA includes but is not limited to carbon tetrachloride, benzene, toluene, dichloroethane, chloroform, acetone, etc.
[0056] In the above scheme, the mass fraction (WT) of PMMA satisfies: 0 <WT≤1wt% In the above solution, the method for preparing the periodic Bragg grating includes but is not limited to laser etching, dry etching and wet etching.
[0057] In the above scheme, the grating satisfies mλ=2nL, m is the grating order, λ is the laser output wavelength, n is the refractive index of the organic-inorganic hybrid perovskite film, and L is the period of the grating.
[0058] In the above solution, the duty cycle of the periodic Bragg grating is 0.25-0.75.
[0059] In the above solution, the pump source is a femtosecond laser or a nanosecond laser.
[0060] In the above solution, the laser is a single-photon or multi-photon pump laser.
[0061] Example 1 Step (1) using a commercial grating reflector (2400 / mm) as a periodic grating structure, placing the grating reflector in deionized water, acetone, and isopropanol for ultrasonic cleaning for 5 minutes, and drying with nitrogen for later use; Step (2) Dissolve 0.7 mmol of cesium iodide (CsI) in 2.5 ml of dimethyl sulfoxide (DMSO), and dissolve 1.071 mmol of methylamine hydroiodic acid (MAI), 5.229 mmol of formamidine hydroiodic acid (FAI), 4.3792 mmol of lead iodide (PbI2), and 1.5008 mmol of lead bromide (PbBr2) in 7.5 ml of N,N-dimethylformamide (DMF), and stir at room temperature for 12 hours.
[0062] Step (3) Pour the above DMSO solution into the DMF solution and continue stirring for 2 hours to prepare an organic-inorganic perovskite precursor solution, which is filtered and set aside.
[0063] Step (4) preparing an acetone solution of PMMA, wherein the mass percentage of PMMA relative to the solvent is 0.5 wt %, and then stirring at room temperature for 12 hours for later use.
[0064] Step (5) Place the commercial reflector on a spin coater at a speed of 500 rpm for 5 seconds. Add the PMMA solution onto the commercial reflector and adjust the spin coater speed to 4000 rpm for 30 seconds. o Anneal at C for 30 min.
[0065] Step (6) Place the commercial reflector with a PMMA layer on the surface of the reflector on a spin coater at a speed of 500 rpm for 5 seconds. Add the organic-inorganic perovskite precursor solution onto the commercial reflector, adjust the spin coater speed to 6000 rpm for 30 seconds. Add the anti-solvent toluene at 20 seconds. Then, heat at 75 o Anneal at C for 30 min.
[0066] Step (7) obtains the laser of the present invention, such as Figure 1 As shown in (a), femtosecond laser and nanosecond laser are used to pump the laser to test the laser performance.
[0067] Figure 2 (a) is a force electron microscope photo of the organic-inorganic hybrid perovskite layer. It is necessary to perform optical testing on the organic-inorganic hybrid perovskite layer to characterize the light gain capability of the perovskite film. The preparation method of the organic-inorganic hybrid perovskite film is as follows: S4-1. Take a highly transparent quartz sheet and place it in deionized water, acetone, and isopropanol for ultrasonic cleaning for 5 minutes, and blow it dry with nitrogen for later use; S4-2. Place the above-mentioned high-transmittance quartz sheet on a spin coater at a speed of 500 rpm for 5 seconds.
[0068] The organic-inorganic perovskite precursor solution obtained in step (3) of Example 1 was dripped onto a high-purity quartz wafer, and the spin coater speed was adjusted to 4000 rpm for 30 seconds. o Annealing was carried out under C conditions for 30 minutes. Then optical testing was performed. Figure 3 (a) is the normalized fluorescence spectrum curve of the organic-inorganic perovskite film. It can be seen from the figure that the obtained emission peak is located near 750nm, which is a typical FA-MA mixed perovskite emission spectrum. Figure 4 As shown in the figure, a FA-MA hybrid perovskite film on a high-purity quartz wafer is pumped by a 400nm femtosecond laser. As the pump power density increases, the spectral intensity increases. When the pump power density is higher than the threshold value of 233.4 μW / cm 2 When the pump power density is further increased, the peak increases rapidly, which indicates the optical gain capability of the FA-MA hybrid perovskite film.
[0069] Example 2 Step (1) using a commercial grating reflector (2400 / mm) as a periodic grating structure, placing the grating reflector in deionized water, acetone, and isopropanol for ultrasonic cleaning for 5 minutes, and drying with nitrogen for later use; Step (2) Dissolve 5 mmol of lead bromide (PbBr2), 4 mmol of formamidine hydrobromide (FABr), and 2 mmol of 1-naphthylmethylammonium bromide (NMABr) in 10 ml of N,N-dimethylformamide (DMF), and stir at room temperature for 12 hours to prepare an organic-inorganic perovskite precursor solution.
[0070] Step (3) Place the commercial reflector on a spin coater at a speed of 500 rpm for 5 seconds. Add the organic-inorganic perovskite precursor solution onto the commercial reflector. Adjust the spin coater speed to 6000 rpm for 30 seconds. Add the anti-solvent ethyl acetate at 20 seconds. Then, heat at 75 o Anneal at C for 30 min.
[0071] Step (4) obtains the laser of the present invention, such as Figure 1 As shown in (b), femtosecond laser and nanosecond laser are used to pump the laser to test the laser performance.
[0072] Figure 2 (b) is a force microscopy photo of the quasi-two-dimensional organic-inorganic hybrid perovskite layer. It is necessary to perform optical testing on the quasi-two-dimensional organic-inorganic hybrid perovskite layer to characterize the optical gain capability of the quasi-two-dimensional perovskite film. The preparation method of the quasi-two-dimensional organic-inorganic hybrid perovskite film is as follows: S5-1. Take a high-transmittance quartz sheet, place it in deionized water, acetone, and isopropanol for ultrasonic cleaning for 5 minutes, and blow it dry with nitrogen for later use; S5-2. Place the above-mentioned high-transmittance quartz sheet on a spin coater at a speed of 500 rpm for 5 seconds.
[0073] The quasi-two-dimensional organic-inorganic perovskite precursor solution obtained in step (2) of Example 2 was dripped onto a high-purity quartz wafer, and the spin coater speed was adjusted to 4000 rpm for 30 seconds. o Annealing was carried out under C conditions for 30 minutes. Then optical testing was performed. Figure 3 (b) is the normalized fluorescence spectrum curve of the quasi-two-dimensional organic-inorganic perovskite film. It can be seen from the figure that the obtained emission peak is located near 550nm, which is a typical quasi-two-dimensional organic-inorganic perovskite emission spectrum.
[0074] Figure 5 The laser spectrum performance of the laser obtained in Example 1 under the action of femtosecond laser pumping is characterized. Under the action of 400nm femtosecond laser pumping, the laser spectrum gradually increases, and a peak with a very narrow half-peak width appears, such as Figure 5 As shown in (a). Considering the background fluorescence enhancement, the spectrum is processed by peak separation (reference Nature Communication 10, 988, 2019. DOI: https: / / doi.org / 10.1038 / s41467-019-08929-0), as shown in Figure 5 As shown in (b), peak A is the background fluorescence part and peak B is the laser gain part. The spectra of the above two peaks are processed by integrated intensity, as shown in Figure 5 As shown in (c), the integrated intensity of peak A increases linearly with the increase of pump power, and its linear fitting coefficient is 0.94, which is consistent with the fluorescence spectrum behavior of single photon (400nm pump). In the low pump power region, the luminescence of peak B remains basically unchanged, but when the pump power is higher than the threshold (0.35μW), the integrated intensity of peak B increases nonlinearly, which is a typical laser phenomenon.
[0075] Figure 6 The quasi-two-dimensional organic-inorganic perovskite film is pumped by a 475nm nanosecond laser. As the pump power density increases, the spectral intensity increases. When the pump power density is higher than the threshold of 6.21 mW / cm 2 When the pump power density is further increased, the peak increases rapidly, indicating the optical gain capability of the quasi-two-dimensional organic-inorganic perovskite film.
[0076] Figure 7The laser spectrum performance of the laser obtained in Example 1 under nanosecond laser pumping is characterized. Under the action of 475nm nanosecond laser pumping, the laser spectrum gradually increases, and a peak with a very narrow half-peak width appears, such as Figure 7 As shown in (a). Considering the background fluorescence enhancement, the spectrum is processed by peak separation, as shown in Figure 7 As shown in (b), peak A is the background fluorescence part and peak B is the laser gain part. The spectra of the above two peaks are processed by integrated intensity, as shown in Figure 7 As shown in (c), the integrated intensity of peak A increases linearly with the increase of pump power, which is consistent with the fluorescence spectrum behavior of single photon (400nm pump). In the low pump power region, the luminescence of peak B remains basically unchanged, while when the pump power is higher than the threshold (311μW / cm 2 ), the integrated intensity of peak B increases nonlinearly, which is a typical laser phenomenon.
Claims
1. An organic-inorganic hybrid perovskite laser based on a DFB structure, characterized in that: include: Pump source: ultraviolet light, blue light source to achieve single-photon pumping or near-infrared light, far-infrared light source to achieve multi-photon pumping; Gain medium: organic-inorganic hybrid perovskite film; Resonant cavity: A substrate with a structure of periodic Bragg gratings.
2. The method for preparing a gain medium of an organic-inorganic hybrid perovskite laser based on a DFB structure according to claim 1, characterized in that: The method for preparing the organic-inorganic hybrid perovskite film comprises the following steps: S1. Weigh MX, FX and PbX2 and dissolve them in solvent to obtain MPbX3 or F2M n-1 Pb n X 3n+1 , precursor with n>1; The organic-inorganic perovskite film is prepared by the S2-1 method or the S2-2 method: S2-1 method, dropping the above precursor solution onto the surface of a rotating substrate, adding an anti-solvent after spin coating, and then annealing to obtain an organic-inorganic hybrid perovskite film; S2-2 method, MX, FX and PbX2 are deposited on the substrate surface by evaporation method, and then annealed to obtain an organic-inorganic hybrid perovskite film; X is a halogen anion; MX is one or two of formamidine hydrohalide and methylamine halide; FX is one or more of benzylamine halide, n-octylamine hydrohalide, isobutylammonium halide, phenylpropylamine halide, aminovaleric acid halide, 1-naphthylmethylammonium halide, guanidine hydrohalide, n-butylamine halide, phenylbutylamine halide, n-butylammonium halide, ethylamine hydrohalide and phenethylamine halide.
3. The preparation method according to claim 2, characterized in that: The solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, γ-butyrolactone and N-methylpyrrolidone.
4. The preparation method according to claim 2, characterized in that: The anti-solvent is one or more of toluene, chloroform, ethanol, chlorobenzene, ethyl acetate, and butyl acetate.
5. The preparation method according to claim 2, characterized in that: The annealing temperature is 50-150 o C, annealing time is 10-120min.
6. The preparation method according to claim 2, characterized in that: In the preparation step S2-1, the anti-solvent is added after spin coating for 5-30 seconds.
7. The preparation method according to claim 1, characterized in that: The substrate is prepared by the S3-1 method or the S3-2 method: S3-1 method uses a periodic Bragg grating structure directly as a substrate; S3-2 Method: (a) Weigh polymethyl methacrylate (PMMA) and dissolve it in a solvent; (b) The PMMA solution is spin-coated on a structure having a periodic Bragg grating, and the resulting composite structure is the substrate.
8. The preparation method according to claim 7, characterized in that: The substrate, the solvent for dissolving PMMA includes but is not limited to carbon tetrachloride, benzene, toluene, dichloroethane, chloroform, acetone, one or more combinations thereof, and the mass fraction WT of PMMA satisfies: 0 <WT≤1wt%。 9. The preparation method according to claim 7, characterized in that: The grating satisfies mλ=2nL, m is the grating order, λ is the laser output wavelength, n is the refractive index of the organic-inorganic hybrid perovskite film, and L is the period of the grating.
10. The preparation method according to claim 6, characterized in that: The duty cycle of the periodic Bragg grating is 0.25-0.75.
Citation Information
Patent Citations
Colloidal quantum dot continuous laser and preparation method thereof
CN108011292A
Distributed feedback quantum dot laser and preparation method thereof
CN118739026A